2015
DOI: 10.1002/aenm.201402180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanoscale Elemental Distribution in High‐Performance Kesterite Solar Cells

Abstract: The effort to develop earth‐abundant kesterite solar cells has led to an approximate doubling of the power conversion efficiency over the past five years to 12.6%, primarily due to increases in short‐circuit current and fill factor; open‐circuit voltage has resisted similar change, limiting further efficiency improvement. In the present investigation, Auger nanoprobe spectroscopy, X‐ray/ultraviolet photoelectron spectroscopy, and device characterization are used to provide a comprehensive understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
153
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(170 citation statements)
references
References 48 publications
16
153
1
Order By: Relevance
“…Shockley-Read-Hall (SRH) recombination on point defects in the bulk of the absorber is generally said to be responsible for this short lifetime 42 but the influence of band tails, grain boundaries or even interfaces on lifetime is rarely discussed 13 . SRH recombination and tunneling-enhanced recombination 38 , grain boundary recombination 43 , low carrier mobility due to defect scattering 46 or carrier localization 50 and insufficient quasi-Fermi level splitting because of too low carrier density 51 or Fermi level pinning 52 are mentioned as well as responsible for this VOC deficit. Moreover, the absence of internal electric field cannot counterbalance these poor electronic properties 43 .…”
Section: Mapping Of Fundamental Failures In Cd-free Kesterite Solar Cmentioning
confidence: 99%
“…Shockley-Read-Hall (SRH) recombination on point defects in the bulk of the absorber is generally said to be responsible for this short lifetime 42 but the influence of band tails, grain boundaries or even interfaces on lifetime is rarely discussed 13 . SRH recombination and tunneling-enhanced recombination 38 , grain boundary recombination 43 , low carrier mobility due to defect scattering 46 or carrier localization 50 and insufficient quasi-Fermi level splitting because of too low carrier density 51 or Fermi level pinning 52 are mentioned as well as responsible for this VOC deficit. Moreover, the absence of internal electric field cannot counterbalance these poor electronic properties 43 .…”
Section: Mapping Of Fundamental Failures In Cd-free Kesterite Solar Cmentioning
confidence: 99%
“…In studies where the annealing treatment is performed in air, the focus is mainly directed to oxidation of grain boundaries [5,8]. It is suggested that SnO x formation in grain boundaries effectively passivate grain boundaries [5]. Another study find that oxygen substitutes for Se in the lattice near grain boundaries [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that the annealing treatment can be used to obtain an appropriate level of Na [7]. In studies where the annealing treatment is performed in air, the focus is mainly directed to oxidation of grain boundaries [5,8]. It is suggested that SnO x formation in grain boundaries effectively passivate grain boundaries [5].…”
Section: Introductionmentioning
confidence: 99%
“…39 The absence of copper at the particle surfaces may be attributed to the formation of CuSO 4 , which is volatile at temperatures much lower than the air annealing temperature.…”
Section: -42mentioning
confidence: 99%
“…Nevertheless, the conclusion from a recent study by Sardashti et al is that the presence of tin-oxide phases and copper-depletion at the surface of the grains in a CZTS thin lm act as a passivating layer, inhibiting charge recombination at grain boundaries. 39 Air annealing CZTS/CZTSSe-based PVs aer production is now commonly applied to enhance device efficiency by this passivation mechanism. 40 Structurally, both of the annealed lms in Fig.…”
mentioning
confidence: 99%